A new model to identify botanical origin of Polish honeys based on the physicochemical parameters and chemometric analysis. (April 2017) - Popek, Stanisław; Halagarda, Michał; Kursa, Karolina
Abstract: Confirmation of the authenticity or adulteration detection is a difficult, laborious and costly process. The aim of this study was to construct a honey botanical origin classification model on the basis of its characteristic physicochemical features. The experimental material comprised of 72 samples of varietal honeys. The botanical origin and the purity of honey samples were verified using a savoriness profiling method, and a pollen analysis. The following parameters of chosen honeys were determined: water, total ash, reducing sugar, total sugar and sucrose content, pH, total acidity solutions, specific electrical conductivity, dynamic viscosity, diastatic number, 5-HMF and proline content. The classification model was constructed with the use of all variables and with an employment of C&RT data mining method. A v-fold cross-validation proved that the model does reproduce the structure of dataset very well and in this particular case, incorrectly classifying only in one case heather honey as a multifloral one. Highlights: Model to identify biological origin of varietal honey was created. Data mining method C&RT proved useful for honey's origin verification model creation. Physicochemical parameters of honey samples were determined. Quality of varietal honeys' samples was evaluated.